Portable Solar Water Pump Design And Forecasting Very Short-Term Sun Light Radiation Using Feed Forward Neural Network Method - Adiwana, Moch. Nur (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2024)
Portable Solar Water Pump is an alternative to renewable energy that can convert solar radiation into the form of electrical energy used to pump rice field irrigation water. Solar radiation promotes increased photovoltaic absorption, leading to improved battery life time performance. Solar cells have a high efficiency value if photons from sunlight can be absorbed as much as possible. This research aims to design a Portable Solar Water Pump. After that analyze the forecasting of solar radiation Watt/ in the next hour starting from 08.00-13.00 then predicted at 14.00 using the Feed-Forward Neural Network (FFNN) method. And get an error value of 2.6. With the highest radiation value of 1285,6 Watt/ . Keywords: Photovoltaic, Portable Solar Water Pump, Solar Radiation, Feed Forward Neural Network